Evaluation of constructs to integrate a legislative code of ethics in México - Arango Morales, Xóchitl A.; Garza Villegas, Juan Baldemar (2014)
Legislators, as public officials, have generated mistrust among citizens because of their behavior, but fundamentally because of their legislative labor. The absence of norm to guide the legislators has caused México to become one of the countries that still has not developed a code of ethics. Given this situation, the objective of this research is to identify the relation and significance among variables individually and in relation to each other. These variables measure the significance and impact within a Code of Ethics. The variables were substantiated through a theoretical framework. For that reason, in the first part of this research each variable is based on a particular framework. The variables for this research are professionalization, accountability, omission, and decision making. Later come the methodological description, analysis and bibliography.